Sharia Fintech Transformation to Encourgae the Inclusivity Growth of Small and Medium Enterprises in Indonesia - Fira Aulia; Muhammad Syukron; Fathul Arifin; Aris Syafi’i; Hendri Hermawan Adinugraha (Universitas Darussalam Gontor, 2024)
Fintech is a business field that provides financial and banking services through the use of technology. The presence of fintech aims to make it easier for people to access financial products and services, including conducting financial transactions. This study aims to understand how fintech innovation can make a significant contribution to financial access and MSME growth. This research is a descriptive qualitative research. This research is a type of library research conducted through the study of various literatures relevant to the research. The results showed that the transformation of Islamic fintech not only provides financial solutions in accordance with sharia principles, but also plays an important role in increasing the inclusiveness of micro, small and medium enterprises. Policy implications and further development directions are discussed to support the implementation of Islamic fintech as a driver of inclusive growth in Indonesia's MSME sector. Keywords: Islamic Financial Technology, MSMEs, Inclusive Finance